Allometry, Function and Shape Diversification in the Inner Ear of Platyrrhine Primates - Río, Joaquín del (2020)
The diversification of anatomical structures with functional importance during the branching process of a clade is a widely studied phenomenon in evolutionary biology. In recent years, there is a growing interest in the study of the inner ear, a structure associated with hearing, locomotion, and indirectly, with body size. These studies have been particularly important in primates. The platyrrhine radiation is an ideal system in which to study inner ear diversification because it is one of the major groups of living primates and an example of an adaptive radiation related to body size and ecological characteristics. In this work, we used micro-tomography, 3D geometric morphometrics, and phylogenetic comparative methods to explore the pattern of shape variation in the inner ear of platyrrhines and to assess whether this variation is related to size, locomotion, and vocalization. Our main results suggest that (1) diversification of inner ear morphology was achieved early in the radiation, particularly for the shape of the semicircular canals and the relative size of the cochlea; (2) inner ear shape diversification is generally not associated with changes in vocalization features or locomotion behaviors; and (3) conversely, body size is a strong predictor of inner ear shape. This last result contrasts with recent studies indicating that allometry has weak effects on platyrrhine cranial diversification and suggests complex factors driving inner ear diversification in the clade.